GAMBARAN JUMLAH LEUKOSIT PADA INDIVIDU YANG TIDUR DI LAMPU MENYALA MENGGUNAKAN ALAT HEMATOLOGY ANALYZER - Shintiani Hadju, Dewi; Dunggio, Yolan; Rachma (LPPM Universitas Bina Mandiri Gorontalo, 2024)
Many individuals still pay little attention to how to sleep well. During sleep, the body will produce the hormone melatonin. Normal production This melatonin hormone in the body can affect the number of leukocytes, especially neutrophils and lymphocytes. So this study aims to describe the number of leukocytes in individuals who sleep with the lights on using a hematology analyzer . The method in this study uses a quantitative approach to the type of research used in this is descriptive. The type of data used is primary data in the form of research results and documentation, as well as questionnaires and informed consent. The sampling technique in this study used a purposive sampling technique, with a total sample of 30 people. The data obtained from the results of this study are presented in the form of tables and narratives and then presented. Based on the results of the research that has been described, it can be concluded that the number of leukocytes in individuals who sleep with the lights on using a hematology analyzer consisting of 30 samples (100%) has a normal leukocyte count.